2010
DOI: 10.1007/s10147-010-0118-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of carboplatin and gemcitabine as adjuvant chemotherapy in patients with completely resected non-small cell lung cancer: a report from the Central Japan Lung Study Group, CJLSG 0503 trial

Abstract: Adjuvant chemotherapy with a carboplatin and gemcitabine combination regimen has an acceptable toxicity profile, and the majority of patients completed 4 cycles of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
1
16
0
2
Order By: Relevance
“…The completion rate of four planned courses of chemotherapy in each of these two phase II trials was 95%, and the incidences of grade 3/4 neutropenia were 18% and 33%, respectively. Furthermore, the CJLSG0503 study showed that adjuvant chemotherapy with a carboplatin/gemcitabine combination regimen also had an acceptable toxicity profile . A randomized trial in 2015 that defined quality of life as the primary end‐point found that cisplatin/gemcitabine or cisplatin/docetaxel adjuvant chemotherapy for completely resected NSCLC was well tolerated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The completion rate of four planned courses of chemotherapy in each of these two phase II trials was 95%, and the incidences of grade 3/4 neutropenia were 18% and 33%, respectively. Furthermore, the CJLSG0503 study showed that adjuvant chemotherapy with a carboplatin/gemcitabine combination regimen also had an acceptable toxicity profile . A randomized trial in 2015 that defined quality of life as the primary end‐point found that cisplatin/gemcitabine or cisplatin/docetaxel adjuvant chemotherapy for completely resected NSCLC was well tolerated .…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of gemcitabine‐containing regimens in efficacy and toxicity over other regimens has been shown in several studies and it has proven to be one of the best regimens for the treatment of advanced NSCLC . Although there is limited prospective phase III clinical trial data, several phase II clinical trials have shown beneficial efficacy and reduced toxicity of cisplatin/gemcitabine as adjuvant chemotherapy . Therefore, we reviewed the charts of 100 patients to investigate the efficacy and toxicities of cisplatin/gemcitabine as adjuvant chemotherapy for patients with completely resected NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies revealed Chemotherapy for stage II-III non-small cell lung cancer [16][17][18] Although GEM combined with platinum has not been used in adjuvant chemotherapy for stage III NSCLC yet, data from the treatment of advanced NSCLC and several clinical trials involving stage II NSCLC with GEM have indicated that the combined treatment of GEM with platinum is more efficacious than NVB therapy in terms of safety and efficacy of postoperative chemotherapy. [19][20][21] This treatment might become a standard scheme of postoperative chemotherapy for NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Less toxic chemotherapy regimens will have the advantages to maintain the quality of life of the patients and to combine them with molecular targeted drugs. The CG combination was tested in various situations of NSCLC patients such as in an adjuvant setting, for the elderly and as a second line for selected patients, showing encouraging effects [13,14,15]. In addition, an acceptable toxicity and promising median overall survival was reported in the combination of CG and bevacizumab for Non-Sq NSCLC [16].…”
Section: Discussionmentioning
confidence: 99%